Acting Places or Places of Action: Gardens in Grimm Brothers’ Children’s and Household Tales - Kheirbek, Dr. Taymaa Hussein (Sulaimani Journal for Humanities, 2023)
Gardens have played a significant role in fairy tales from the dawn of recorded history since they are seen as symbols that form a repository of folkloric knowledge. The Grimm Brothers were aware of the natural unity that can be found in the gardens. Therefore, they considered them spaces of great potential which can create romantic atmospheres, promote healing and learning, and even send characters into magical lands. In literary analysis, the subject-centric perspective can be seen as dominant in fairy tales. There is a constant focus on the characters and the actions, while totally ignoring the significance of place. Despite the constant attempts to prioritize content over other elements of the plot, spatial studies emerged as an important branch of studying literature. To challenge this attention to subjectivity, this paper sheds light on the spatial aspects and its role in shaping the story. It focuses on analyzing the types and functions of gardens in Grimm Brother’s Children and Household Tales. It also demonstrates how gardens are used as a device for character and plot development. The theoretical framework is based on literary spatial studies. Animals, flowers, trees, and supernatural creatures will also be investigated and discussed as inhabitants of gardens and participants in the narrative structure.
Keywords: Garden; Place; Grimm Brothers; Spatial studies; Fairy tales; Childrens Literature